PHYSICAL MODELING OF MOLECULAR DISTRIBUTION ON THE LATERAL SURFACE OF A HEMISPHERICAL WATER DROPLET AND THE EVAPORATION PROCESS (Scientific journal of the Fergana State University, 2026)
In this paper, a new model was developed to determine the number of molecules located on the surfaces of hemispherical and segmental water droplets based on physical principles. The aim of the study is to ensure the modeling of molecular distribution over the droplet surface using precise physical parameters. The model calculates the number of molecules based on the droplet radius, the density and molar mass of water, and Avogadro‘s number. In the methodology, the determination of the number of surface molecules is based on the integration of geometric parameters and molecular physical constants. Experimental measurements were carried out at a temperature of 25°C and a relative humidity of 20%, assessing how the droplet volume and surface molecule count change over time. The results showed that the number of molecules decreases exponentially and that the evaporation process is closely related to the reduction of the droplet surface area. While previous algebraic models relied on idealized conditions without considering real physical factors, the proposed model enables a more accurate characterization of molecular distribution through physically grounded parameters.